Flipped classroom approach in rigid body dynamics: A case study of five-semester observation - Hassan, M. H. A.; Othman, N. A. (Kassel University Press GmbH, 2021)
The flipped classroom is an alternative approach to the conventional lecture by introducing collaborative tasks in the class to promote active learning. The theoretical lecture was delivered to the students through videos, which they watch at home before the class. The implementation of this method at the undergraduate level especially in engineering courses was reported to be lacking. This study presents a five-semester observation in the Rigid Body Dynamics course, during which the first two semesters were conducted using the conventional approach, and the following three semesters were flipped. Three indicators were measured to evaluate the effectiveness of the method: the percentage of failures, the number of student enrolments, and the lecturer evaluation score. There is strong evidence showing that flipped classroom has increased the student's performance. Also, it was found that the students prefer this method compared to the conventional approach. This study demonstrates that the flipped classroom approach can be implemented in engineering courses with a good chance of success.